Diode-pumped continuous-wave Nd:GSGG laser at 1102.9 nm. (17th October 2018) - Lin, Hongyi; Liu, Hong; Li, Yukun; Sun, Dong
Abstract: We report an efficient continuous-wave Nd:GSGG laser at 1102.9 nm for the first time. The output power is 2112 mW at a pump power of 10.3 W with a conversion efficiency of 20.5%. The main peak line at 1061.4 nm is completely suppressed by a special output mirror with high transmission at 1061 nm.